Optimal control theory : an introduction - Kirk, Donald E., 1937- (Dover Publications, 2004)
Geared toward upper-level undergraduates, this text introduces three aspects of optimal control theory: dynamic programming, Pontryagin's minimum principle, and numerical techniques for trajectory optimization. Numerous problems, which introduce additional topics and illustrate basic concepts, appear throughout the text. Solution guide available upon request. 131 figures. 14 tables. 1970 edition.
Originally published: Englewood Cliffs, N.J. : Prentice-Hall, 1970 (Prentice-Hall networks series).
Keywords: Control theory.; Mathematical optimization.; elektronické knihy; electronic books